2019
DOI: 10.1080/21645515.2019.1593085
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination against autoimmune diseases moves closer to the clinic

Abstract: Biologicals, e.g. TNF inhibitors, have improved dramatically the efficacy of medical interventions in autoimmune diseases, such as in rheumatoid arthritis (RA). However, although progressive inflammation can be halted in this way, no drug-free remissions or lasting cures are reached. For this to become real, therapies based on induction antigen-specific immune tolerance are sought. This review describes mechanisms of tolerance and the current possibilities for induction of therapeutic tolerance through antigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
0
7
0
1
Order By: Relevance
“…Increases in the number and inhibitory activity of Treg cells changed the immune response to Th2 subsets vivo is better than in vitro expansion, and thus they have attempted to combine the two approaches, such as the application of autoantigen in an incomplete adjuvant (137), and the combination of tolDCs and Treg-induced peptide, which inactivate effector cells and promote the function of Treg cells (138).…”
Section: Factors Induce the Inhibition Of Soluble Protein Secretion Bmentioning
confidence: 99%
“…Increases in the number and inhibitory activity of Treg cells changed the immune response to Th2 subsets vivo is better than in vitro expansion, and thus they have attempted to combine the two approaches, such as the application of autoantigen in an incomplete adjuvant (137), and the combination of tolDCs and Treg-induced peptide, which inactivate effector cells and promote the function of Treg cells (138).…”
Section: Factors Induce the Inhibition Of Soluble Protein Secretion Bmentioning
confidence: 99%
“…Numerous studies have demonstrated that the administration of soluble antigens or immunodominant peptides under non-inflammatory conditions can indeed induce a state of unresponsiveness. Clonal deletion, induction of anergy, or modification in the cytokine profile of pro-inflammatory effector cells and, notably, induction and expansion of regulatory T cells (Tregs) were discussed as possible mechanisms in induced tolerance ( 3 8 ). Tregs play a pivotal role in maintaining self-tolerance and in modulating immune responses in inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…146 Moreover, the combination of tolergenic dendritic cell (tolDC) and Treg-inducing peptides to inactivate effector cells, promotes Treg cell function. 147…”
Section: Limitations Of Treg Therapymentioning
confidence: 99%